'..It takes a lot of brain space': Understanding young carers' lives in England and the implications for policy and practice to reduce inappropriate and excessive care work. (18th August 2021) - Margaret Gowen, Sara; Sarojini Hart, Caroline; Sehmar, Permala; Wigfield, Andrea
Abstract: This qualitative study, undertaken in England, explored young carers' perspectives on the nature of their caring responsibilities. The findings are significant, particularly in the context of England's Care Act 2014, which seeks to prevent children engaging in 'excessive' or 'inappropriate' caring. Our research placed children at the heart of the debate on what constitutes appropriate care. The findings raise key questions regarding effective implementation of contemporary child policy, duties of care towards children in caring roles and priorities for child protection and family support policy and practices, with the potential to inform thinking around child's well‐being in wider contexts.